2018
DOI: 10.4102/sajhrm.v16i0.825
|View full text |Cite
|
Sign up to set email alerts
|

Research trends in the <i>South African Journal of Human Resource Management<i>

Abstract: Orientation: A comprehensive framework for research in human resource management (HRM) in terms of fundamental knowledge orientations was found lacking.Research purpose: The aim was to perform a typological review of research trends in the field of HRM, specifically of publications in the South African Journal of Human Resource Management (SAJHRM).Motivation for the study: No previous research in the field of HRM in South Africa adopted a fundamental theory of knowledge.Research design, approach and method: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…These results suggest that entrepreneurship may be a self-reinforcing process where the degree of entrepreneurial activities is an outcome of a dynamic process in which SV are as important as legal and economic factors in determining levels of entrepreneurial activity (Bygrave & Minniti, 2000). From this perspective, the importance of recognising the influence of prevailing SV as embedded in regional and local communities is vital for understanding innovation in the African context (Pietersen, 2018). If entrepreneurship is not valued in terms of the SV of a particular country, then not only will it be associated with criminality and corruption, but other forms of economic pursuits will also prove unproductive and ineffective (Venter & Urban, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…These results suggest that entrepreneurship may be a self-reinforcing process where the degree of entrepreneurial activities is an outcome of a dynamic process in which SV are as important as legal and economic factors in determining levels of entrepreneurial activity (Bygrave & Minniti, 2000). From this perspective, the importance of recognising the influence of prevailing SV as embedded in regional and local communities is vital for understanding innovation in the African context (Pietersen, 2018). If entrepreneurship is not valued in terms of the SV of a particular country, then not only will it be associated with criminality and corruption, but other forms of economic pursuits will also prove unproductive and ineffective (Venter & Urban, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Landers and Behrend (2015) add that coverage of external validity is limited in research education and research textbooks. This lack of interest has further limited literature on external validity as well as the application of research findings to practice (Steckler & McLeroy, 2008) which has become a worldwide phenomenon (Pietersen, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Visser and Van Staden (1990) reviewed the sampling method used in SAJIP from 1979 to 1988 and found that only 3% of the samples was described, 53% used non-random sampling whilst 25% of the articles indicated no sampling strategy. Except for Visser and Van Staden's 1990 review of a South African journal, reviews of sampling methods used in psychology in Africa are lacking (see O'Neil & Koekemoer, 2016;Pietersen, 2018;Schreuder & Coetzee, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent work on South Africa has highlighted the limitations of formal training and persistent skills gaps (Horwitz, 2017). As with many other contexts, there remains a widespread gap between formalized conceptualizations of managing knowledge and people, and improvised solutions on the ground, which may not be easily replicable (Pietersen, 2018). However, there are also historical and contextual anomalies that pose even more serious challenges to effective talent management.…”
Section: The South African Casementioning
confidence: 99%